Review: Myopathies in broilers: supply chain approach to provide solutions to challenges related to raising fast growing birds - Shai Barbut; Randolph Mitchell; Parker Hall; Craig Bacon; Ritchard Bailey; Casey M. Owens; Massimiliano Petracci (Poultry Science, 2024)
ABSTRACT: This review is a summary of a Poultry Science Association symposium addressing myopathies in broilers’ breast meat, focusing on the interactions between genetics, nutrition, husbandry, and meat processing. The Pectoralis major myopathies (woody breast [WB]; white striping [WS]; spaghetti meat [SM]) and Pectoralis minor (“feathering”) are described, followed by discussing their prevalence, potential causes, current and future ways to mitigate, as well as detection methods (in live birds and meat) as well as ways to utilize affected meat. Overall, breast myopathies remain an important focus across the poultry industry and whilst a lot of data and knowledge has been gathered, it is clear that there is still a lot to understand. As there are multiple factors impacting the occurrence of breast myopathies, their reduction relies on a holistic approach. Ongoing balanced breeding strategies by poultry breeders is targeting the longer-term genetic component but comprehending the significant influence from nongenetic factors (short-term solutions such as nutrition) remains a key area of opportunity. Consequently, understanding the physiology and biological needs of the muscle through the life of the bird is critical to reduce the myopathies (e.g., minimizing oxidative stress) and gain more insight into their etiology.